Menuju Demokrasi Substantif: Inklusi Disabilitas dan Partisipasi Politik dalam Pilkada Makassar 2024 - Sari, Endang; Rafly, Rafly (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This study highlights significant challenges in fulfilling the political rights of persons with disabilities. Persistent barriers to accessibility remain, including limited physical facilities at polling stations, inadequate preparedness of election officials, substandard assistive tools such as poorly legible Braille templates, and insufficient access to information across diverse disability categories. The research aims to describe and analyze the actual conditions of accessibility and patterns of political participation among persons with disabilities during the 2024 Makassar local elections. Employing a qualitative descriptive approach, data were collected through in-depth interviews with key informants, including voters with disabilities, election organizers (KPU, Bawaslu), and representatives of disability organizations. Findings reveal a gap between normative instructions issued by election authorities and practices in the field. Although voter turnout among persons with disabilities increased by 77% compared to 2020, physical accessibility—such as the availability of ramps—remains uneven, and Braille templates are often difficult to read independently. In terms of participation, a layered pattern emerges: the majority engage at the basic level (voting), while a smaller group actively participates in policy forums such as Musrenbang. Their motivations vary, ranging from autonomous awareness to test inclusivity, to mobilization driven by material proximity or community solidarity. The study concludes that strengthening inclusion requires strategic measures, including specialized training for election officials, standardized disability-friendly facilities across all polling stations, and systematic evaluation of assistive tools. These steps are crucial to ensuring that the political rights of persons with disabilities are substantively fulfilled, thereby enriching the quality of local democracy